Social prescribing for migrants in the United Kingdom: A systematic review and call for evidence - Claire X. Zhang; Fatima Wurie; Annabel Browne; Steven Haworth; Rachel Burns; Robert Aldridge; Dominik Zenner; Anh Tran; Ines Campos-Matos (Elsevier, 2021)
Background: The health needs of international migrants living in the United Kingdom (UK) extend beyond mainstream healthcare to services that address the wider determinants of health and wellbeing. Social prescribing, which links individuals to these wider services, is a key component of the UK National Health Service (NHS) strategy, yet little is known about social prescribing approaches and outcomes for international migrants. This review describes the evidence base on social prescribing for migrants in the UK. Methods: A systematic review was undertaken, which identified studies through a systematic search of 4 databases and 8 grey literature sources (January 2000 to June 2020) and a call for evidence on the UK government website (July to October 2020). Published and unpublished studies of evaluated social prescribing programmes in the UK were included where at least 1 participant was identified as a migrant. Screening, data extraction and quality appraisal were performed by one reviewer, with a second reviewer checking 20% of studies. A narrative synthesis was conducted. Findings: Of the 4544 records identified, 32 were included in this review. The overall body of evidence was low in quality. Social prescribing approaches for migrants in the UK varied widely between programmes. Link workers who delivered services to migrants often took on additional support roles and/or actively delivered parts of the prescribed activities themselves, which is outside of the scope of the typical link worker role. Evidence for improvements to health and wellbeing and changes in healthcare utilisation were largely anecdotal and lacked measures of effect. Improved self-esteem, confidence, empowerment and social connectivity were frequently described. Facilitators of successful implementation included provider responsiveness to migrants' preferences in relation to language, culture, gender and service delivery format. Barriers included limited funding and provider capability. Conclusions: Social prescribing programmes should be tailored to the individual needs of migrants. Link workers also require appropriate training on how to support migrants to address the wider determinants of health. Robust evaluation built into future social prescribing programmes for migrants should include better data collection on participant demographics and measurement of outcomes using validated and culturally and linguistically appropriate tools. Future research is needed to explore reasons for link workers taking on additional responsibilities when providing services to migrants, and whether migrants' needs are better addressed through a single-function link worker role or transdisciplinary support roles.